2021
DOI: 10.1007/s11295-021-01502-1
|View full text |Cite
|
Sign up to set email alerts
|

ABA influences color initiation timing in P. avium L. fruits by sequentially modulating the transcript levels of ABA and anthocyanin-related genes

Abstract: In sweet cherry, as in most non-climacteric species, abscisic acid (ABA) plays a major role in the control of fruit ripening and color development. Although the ABA treatment of sweet cherry fruits has been reported to upregulate anthocyanin pathwayrelated genes or ABA pathway-related genes, the temporality of molecular and physiological events occurring during color development and the ABA control of these events during the color initiation are lacking in this species. In this work, we analyzed variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…It is well known that ABA increases color due to an increase in the accumulation of anthocyanins in sweet cherry 13,15,16 and in other non-climacteric fruits such as grapes 10 and strawberry 9,12 . We have also seen fruit color changes in the 'Lapins' cultivar when the tree canopy was sprayed with ABA 17 , and similar results were found in the seasons that we report in this paper. However, here we have also compared this response in 'Lapins' with other cultivars during the same season.…”
Section: Cultivar Dependent Effect Of Aba Canopy Spraying Of Sweet Cherry Trees On Fruit Quality Parameterssupporting
confidence: 88%
See 2 more Smart Citations
“…It is well known that ABA increases color due to an increase in the accumulation of anthocyanins in sweet cherry 13,15,16 and in other non-climacteric fruits such as grapes 10 and strawberry 9,12 . We have also seen fruit color changes in the 'Lapins' cultivar when the tree canopy was sprayed with ABA 17 , and similar results were found in the seasons that we report in this paper. However, here we have also compared this response in 'Lapins' with other cultivars during the same season.…”
Section: Cultivar Dependent Effect Of Aba Canopy Spraying Of Sweet Cherry Trees On Fruit Quality Parameterssupporting
confidence: 88%
“…The exogenous application of ABA in sweet cherry fruits had been studied nearly 30 years ago 13 . Previously the role of ABA on sweet cherry fruit maturity has usually been studied in early-maturing cultivars (Satonishiki, Hongdeng, Prime Giant) 13,16,23 , with only a few experiments in other mid-maturing cultivars such as 'Bing' 19 and 'Lapins' 17 . Regardless of this, the exogenous application is not a common agronomic practice in sweet cherry in comparison to other growth regulators such as gibberellin (GA3) 18,[24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mid-maturing sweet cherry variety Lapins, we previously found that GA 3 increases PavPP2C3 and PavPP2C4 transcripts and delays the increase in the ripening index, IAD 17 , supporting the present findings. Contrary to GA 3 , we recently showed that ABA treatment advances the IAD increase related to PavNCED1 transcript abundance accumulation and ABA content increase 45 . These results suggest a switch for the control of ripening timing where ABA advances and GA 3 delays the ripening initiation in sweet cherry fruits.…”
Section: Discussionmentioning
confidence: 85%
“…The exogenous application of ABA in sweet cherry fruits had been studied nearly 30 years ago [11]. Previously the role of ABA on sweet cherry fruit maturity has usually been studied in early-maturing cultivars ('Satonishiki', 'Hongdeng', 'Prime Giant') [11,14,21], with only a few experiments in other mid-maturing cultivars such as 'Bing' [17] and 'Lapins' [15]. Regardless of this, the exogenous application is not a common agronomic practice in sweet cherry in comparison to other growth regulators such as gibberellin (GA 3 ) [16,[22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%